Harmonic univalent functions Ssarlike or convex of complex order - Yasar, Elif
We consider a generalized class SH(m, b) which is constructed by modified Salagean operator. The object of the present paper is to study some relations between classes of harmonic univalent functions which are starlike or convex of complex order and other classes of harmonic univalent functions and to give an answer to a conjecture due to Owa [9] in harmonic case.
Keywords: Harmonic; Starlike; Convex; Modified salagean operator